DESCUBRIENDO EL TALENTO DEPORTIVO EN EL BOXEO AMATEUR: CAMINO A LA REALIDAD - Kalpachki, Blagoi (Revista Observatorio del Deporte, 2016)
This study focuses on the necessity of elaborating a multidimensional system for discovering talented children and their guidance to the boxing field, being an overly significant factor, which effects on both th e effectiveness of the next stages of the overall process of sports selection and orientаtion, as well on the future sports achievements and self-realization of these children. Considering the analysis of the data from survey conducted among 83 experts аnd trainers in the boxing field in Republic of Bulgaria, it was found that such a multidimensional system for discovering childre with аbilities for getting good results in the amateur boxing field currently, does not exist. The sports selection is carried out once after the children have been guided to boxing and have systematically begun to practice this type of activity.